Factors affecting hedgehog (Erinaceus europaeus) attraction to rural villages in arable landscapes - Pettett, C; Moorhouse, T; Johnson, P; Macdonald, D (Springer Berlin Heidelberg, 2017)
Although residential areas are often unfavourable for wildlife, some species can take advantage of the available shelter and anthropogenic sources of food such as supplementary feeding. The European hedgehog (Erinaceus europaeus) is increasingly associated with gardens and villages and less so with arable farmland. Suggested drivers for this include the following: hedgehogs’ attraction to higher food densities, including natural prey and anthropogenic sources, a greater range of day nest sites and warmer microclimates in rural villages, coupled with decreased risk of predation by badgers (Meles meles). We investigated the contribution of these drivers by radio-tracking hedgehogs on four arable sites, two with badgers present. Seventy-eight hedgehogs were tracked, 32 yielding enough data to calculate home range sizes. At the home range and landscape scales, gardens and buildings were the highest ranked habitats compared with their availability. Woodland and arable land were the lowest ranked compared with their availability. Villages were the most selected habitat for nesting. When hedgehogs were found closer to buildings, their ranges were smaller and we speculate this is due to increased food availability in villages. Where badgers were present hedgehogs remained closer to cover and their home ranges were on average 12.2 ha smaller. On badger-occupied sites, 50% fewer radio-tracking fixes were on arable land. We conclude that resource availability coupled with nest site selection and badger presence drives hedgehogs’ selection of rural villages. We found no effect of ambient temperature on habitat use. We recommend focusing conservation efforts on maintaining hedgehog populations in rural villages.